Pembuatan dan Karakterisasi Rochelle Salt Crystal - M. Wafieq Akbar Al Asyrafi; Adrianus Inu Natalisanto; Rahmat Gunawan (Progressive Physics Journal, 2021)
Rochelle Salt is the first synthesis Crystal made by Pierre Siegnette La Rocchelle in France. Rochelle Salt have several characteriztion one of them is piezoelectric effect where the crystal can change the kinetic energy to electrical energy instead this is the one of rewenable source altenative energy. Rochelle Salt can be made with tartar cream and washing soda reacted with distilled water as a solvent. The solution is reacted until there is no more reaction or supersaturation condition. Wait the solution for 2 days until the crystal seed appears. The crystal growth using the method of growing crystal in solution for 1 month until the crystal bigger enough for research to find the piezoelectric effect. Based on the result that have been obtained, Rochelle Salt have piezoelectric effect. Crystal hit using with wooden hitter and metal hitter, the voltage is increase when the crystal is hit by hitter. The piezoelectric also disappear along with time.